Replacing the SpCas9 HNH domain by deaminases generates compact base editors with an alternative targeting scope - Villiger, Lukas; Schmidheini, Lukas; Mathis, Nicolas; Rothgangl, Tanja; Marquart, Kim; Schwank, Gerald (Molecular therapy. Nucleic acids, 2021)
Base editors are RNA-guided deaminases that enable site-specific nucleotide transitions. The targeting scope of these Cas-deaminase fusion proteins critically depends on the availability of a protospacer adjacent motif (PAM) at the target locus and is limited to a window within the CRISPR-Cas R-loop, where single-stranded DNA (ssDNA) is accessible to the deaminase. Here, we reason that the Cas9-HNH nuclease domain sterically constrains ssDNA accessibility and demonstrate that omission of this domain expands the editing window. By exchanging the HNH nuclease domain with a monomeric or heterodimeric adenosine deaminase, we furthermore engineer adenine base editor variants (HNHx-ABEs) with PAM-proximally shifted editing windows. This work expands the targeting scope of base editors and provides base editor variants that are substantially smaller. It moreover informs of potential future directions in Cas9 protein engineering, where the HNH domain could be replaced by other enzymes that act on ssDNA. [Display omitted] We reason that the Cas9-HNH nuclease domain sterically constrains ssDNA accessibility at PAM-proximal positions. Replacing the HNH domain of SpCas9 with adenosine deaminases results in size reduced base editors with PAM proximally shifted editing windows (HNHxABE). These base editors enable nucleotide transitions of previously difficult-to-target SNPs.